The Effect of Integrity, Independence, and Competence on Audit Quality at the Regional Inspectorate of Bandung Regency - Risma Trinur Pebriyanti; Romli Romli (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of integrity, independence, and competence of internal auditors on audit quality at the Bandung Regency Regional Inspectorate. The background of the study is based on the results of the 2024 APIP Capability Evaluation by the BPKP Representative of West Java Province, which shows that the Bandung Regency Regional Inspectorate is still at Level 3, with several Areas of Improvement, especially in the implementation of compliance audits and performance audits that are not optimal in producing strategic and sustainable recommendations. This study uses a quantitative method with a sample of 65 internal auditors and multiple linear regression data analysis techniques. The results show that integrity does not significantly affect audit quality, while independence and competence have a positive and significant effect on audit quality. Simultaneously, integrity, independence, and competence have a significant effect on audit quality. These findings indicate that improving audit quality within the Bandung Regency Regional Inspectorate is more influenced by strengthening the independence and competence of internal auditors.